2015
DOI: 10.1002/btpr.2082
|View full text |Cite
|
Sign up to set email alerts
|

A simplified and robust protocol for immunoglobulin expression in Escherichia coli cell‐free protein synthesis systems

Abstract: Cell‐free protein synthesis (CFPS) systems allow for robust protein expression with easy manipulation of conditions to improve protein yield and folding. Recent technological developments have significantly increased the productivity and reduced the operating costs of CFPS systems, such that they can compete with conventional in vivo protein production platforms, while also offering new routes for the discovery and production of biotherapeutics. As cell‐free systems have evolved, productivity increases have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 42 publications
0
93
0
Order By: Relevance
“…164 This lead to a systematic re-examination of the optimal concentration of the essential components of the cell-free protein synthesis reaction mixture, which resulted in a 95% reduction in reagent costs. 165 These results, while obtained using an antibody as a model, are likely to be applicable to other recombinant immunotherapeutic molecules and vaccine antigens.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 84%
“…164 This lead to a systematic re-examination of the optimal concentration of the essential components of the cell-free protein synthesis reaction mixture, which resulted in a 95% reduction in reagent costs. 165 These results, while obtained using an antibody as a model, are likely to be applicable to other recombinant immunotherapeutic molecules and vaccine antigens.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 84%
“…The cost of protein prototyping from this in vitro method is competitive especially when one uses scalable extract preparation techniques as noted above (Dopp & Reuel, ) and minimal reagent recipes (Cai et al, ; Calhoun & Swartz, ; Jewett & Swartz, ; Kim et al, ). When analyzing the cost per gram of sfGFP produced (Supporting Information Figures S10), we found a minimalist reagent mix, like those used in previous works (Cai et al, ; Dopp & Reuel, ), produced sfGFP at 110 µg/ml (found by fluorescence calibration curve Figure S12) after 4 hr of expression which resulted in $61/mg sfGFP. When using a vendor kit, such as Promega T7 S30 High‐Yield with the minimalist, circular templates a 64% decrease in protein yield (40 µg/ml) was observed (Supporting Information Figure S11) which resulted in a 135‐fold increase in cost ($8,265/mg sfGFP; Supporting Information Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Cell‐free expression with E. coli extract cannot form disulfide bonds between cysteine residues without changing the redox potential. Disulfide bonding is commonly achieved through the pretreatment of extract with iodoacetamide, the addition of glutathione, and the addition of disulfide bond isomerase C (DsbC; Cai et al, ). However, this limitation can be overcome by mutating cysteines involved with disulfide bonding as long as the bonds are not necessary for protein structure and function (Lu, Welsh, & Swartz, ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell-free energy mixes can also be simplified through the rational testing and removal of unnecessary components that upon re-examination are largely historical artefacts from protocols that have now been superseded by improved cell-free methodologies. Such approaches have been used to develop minimal energy mixes that maintain cell-free performance but with seven fewer energy components than widely reported cell-free protocols (Cai et al, 2015).…”
Section: Development Of a Whey Permeate-based Cell-free Energy Systemmentioning
confidence: 99%
“…Upon consideration of several cell-free methodologies, a fairly simplified cell extract preparation workflow was used in this study adapted from our previous cell-free work and coupled with a recently reported glutamate-based minimal energy mix (Cai et al, 2015). Using these cell-free methods several batches of E. coli MG1655 TX-TL cell extracts and minimal energy mix were generated (see materials and methods 2.3 and 2.4).…”
Section: Development Of a Whey Permeate-based Cell-free Energy Systemmentioning
confidence: 99%